Integrated In Vivo Quantitative Proteomics and Nutrient Tracing Reveals Age-Related Metabolic Rewiring of Pancreatic β Cell Function - Matthew Wortham; Jacqueline R. Benthuysen; Martina Wallace; Jeffrey N. Savas; Francesca Mulas; Ajit S. Divakaruni; Fenfen Liu; Verena Albert; Brandon L. Taylor; Yinghui Sui; Enrique Saez; Anne N. Murphy; et al. (Cell Reports, 2018)
Summary: Pancreatic β cell physiology changes substantially throughout life, yet the mechanisms that drive these changes are poorly understood. Here, we performed comprehensive in vivo quantitative proteomic profiling of pancreatic islets from juvenile and 1-year-old mice. The analysis revealed striking differences in abundance of enzymes controlling glucose metabolism. We show that these changes in protein abundance are associated with higher activities of glucose metabolic enzymes involved in coupling factor generation as well as increased activity of the coupling factor-dependent amplifying pathway of insulin secretion. Nutrient tracing and targeted metabolomics demonstrated accelerated accumulation of glucose-derived metabolites and coupling factors in islets from 1-year-old mice, indicating that age-related changes in glucose metabolism contribute to improved glucose-stimulated insulin secretion with age. Together, our study provides an in-depth characterization of age-related changes in the islet proteome and establishes metabolic rewiring as an important mechanism for age-associated changes in β cell function. : Organismal age impacts fundamental aspects of β cell physiology. Wortham et al. apply proteomics and targeted metabolomics to islets from juvenile and adult mice, revealing age-related changes in metabolic enzyme abundance and production of coupling factors that enhance insulin secretion. This work provides insight into age-associated changes to the β cell. Keywords: β cell, SILAM MudPIT mass spectrometry, quantitative proteomics, insulin secretion, β cell maturation, aging, isotope tracing, triggering pathway, amplifying pathway, TCA cycle